Cement Mould and Metallic Endoskeleton for Treatment of Hip Infection, an Inexpensive Alternative: A Preliminary Report of Two Cases - Choo, Ch'ng Hwei; Simmrat, Singh; Suhaeb, Abdulrazzaq Mahmod (Malaysian Orthopaedic Association, 2017)
Infection of the hip after implant fixation is an uncommon yet devastating complication that results in poor long-term outcome. The gold standard treatment for chronic infection after hip arthroplasty is a two-stage protocol: eradication of infection, follow by re-implantation arthroplasty. The use of interim antibiotic-laden cement spacer has become a popular procedure to maintain hip joint function and provide antibiotic elution simultaneously before re-implantation. However, antibiotic cement spacer is mechanically weak and breaks if overloaded. Therefore, we designed a cement mould with metallic endoskeleton with the aim of creating a stronger, inexpensive, antibiotic-impregnated spacer resembling a unipolar arthroplasty. We report two cases of severe hip joint infection after implant fixation (bipolar hemiarthroplasty, screw fixation neck of femur). Both patients had undergone first stage surgery of debridement and articulating antibiotic cement insertion using our design. Although the second stage surgery was planned for these patients, both patients delayed the operation in view of good functional status after a year walking with the antibiotic cement spacer. These cases showed that the mechanical property of the new antibiotic cement spacer was promising but further mechanical studies upon this new endoskeleton design are required.